THE UTILIZED OF ULIN WOOD WASTE (Eusideroxylon Zwageri T) AS ACTIVE CHARCOAL TO ADSORB IRON (Fe) AND MANGANESE (Mn) - Mirwan, Agus; Pratidina, Niska Nana; Sari, Anna Permana (Konversi, 2018)
Abstract- A research on the utilization of ulin wood waste (Eusideroxylon Zwageri T) has been conducted as an active charcoal to adsorb Iron (Fe) and Manganese (Mn). The purpose of this research is to know and study the potential of activated charcoal from Ulin wood waste as adsorbent of Iron (Fe) and Manganese (Mn) in well water, knowing optimum time to adsorb Iron (Fe) and Manganese (Mn) and to know the concentration of Iron (Fe) and Manganese (Mn) after adsorbed by activated charcoal from Ulin wood waste. Charcoal is obtained from Ulin wood with burning for 9 hours, then activated chemically and physics. The parameters studied were pH, optimum time determination, Iron (Fe) and Manganese (Mn) concentration after adsorption. The results showed that the optimum time (toptimum) to adsorb Iron (Fe) and Manganese (Mn) was at minute 30 and obtained the optimum concentration of Iron (Fe) of 0,22 mg / L and Manganese (Mn) Â concentration of 0,174 mg / L .Â Keywords: Ulin Wood, activated charcoal, Fe and Mn adsorption, filtration.Â